Effects of Cardiotoxins on Cardiac Stem and Progenitor Cell Populations - Smith, Andrew J. (Frontiers in Cardiovascular Medicine, 2021)
As research and understanding of the cardiotoxic side-effects of anti-cancer therapy expands and the affected patient population grows, it is important to consider the full range of myocardial cell types affected. While direct impacts of these toxins on cardiac myocytes constitute the most immediate damage, over the long-term the myocardial ability to repair or adapt to this damage becomes an ever greater component of the disease phenotype. One aspect is the potential for endogenous myocardial repair and how it may be limited by cardiotoxins depleting the cells contributing to this. Clear evidence exists of new cardiomyocyte formation in adult human myocardium, along with the identification in the myocardium of endogenous stem/progenitor cell populations with pro-regenerative properties. Any cardiotoxin effects on either process will worsen long-term prognosis. While the role of cardiac stem/progenitor cells in cardiomyocyte renewal appears at best limited, there are strong indications of pro-regenerative action through supporting survival of injured cells. A number of recent studies have identified detrimental impacts of anti-cancer therapies on cardiac stem/progenitor cells, with negative effects of both long-established chemotherapy agents (e.g. doxorubicin) and newer, less overtly cardiotoxic agents (e.g. tyrosine kinase inhibitors). Damaging impacts are seen directly on cell numbers and viability, but also on these cells’ ability to maintain the myocardium through generating pro-survival secretome and differentiated cells. We present a review of the identified impacts of cardiotoxins on cardiac stem and progenitor cells, considered in the context of likely roles played by these cells in the maintenance of myocardial tissue homeostasis.